(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2022)
The study was conducted to show the effect of using dried rumen powder as a source of animal protein in the diets of common carp (Cyprinus carpio L.) on its performance, in the fish laboratory/College of Agricultural Engineering Sciences/University of Baghdad/ for a period of 70 d, 70 fingerlings were used with an average starting weight of 30±3 g, with a live mass rate of 202±2 g, randomly distributed among five treatments, two replicates for each treatment and seven fish for each replicate. Five diets of almost identical protein content and different percentages of addition of dried rumen powder were added. 25% was added to treatment T2 and 50% to treatment T3 and 75% of the treatment T4 and 100% of the treatment T5 In addition to the control treatment T1, which was devoid of dried rumen powder, the fish were fed on experimental diets of 4% of their body weight and weighed every 15 d. The results showed that the T2 treatment was one of the best experimental treatments, as it gave the highest levels for most of the studied traits. The results indicated that there were significant differences (p>0.01) and (P < 0.05) between it and the control treatment T1 in growth parameters, which included the final weight average of 715 g and the rate of increase The total weight is 512.50 g, the daily weight gain rate is 12.32 g/d, the relative growth rate is 252.47%, and the specific growth rate is 1.75 g/d. The criteria for evaluating the diet, which included the amount of feed intake 1765.26 g and the amount of protein intake 577.41 g, and the best food conversion ratio of 3.44 and the efficiency of food conversion was 29.03 % and the value of the protein produced is 64.21% and the net exploited protein is 0.73%. We conclude from the current study that the dried rumen powder can be used by 25% in the diets of common carp (Cyprinus carpio L.) as a partial substitute for imported animal protein because it contributed to improving production performance. It can also be used Dried rumen powder at rates of 50 and 75%, but did not reach the levels achieved by 25%.